Interstitial lung disease in the elderly: pathogenesis, diagnosis and management - Meyer, K.C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Advancing age is associated with increased risk for some forms of interstitial lung disease (ILD), and this risk is especially reflected by the considerably increased incidence of idiopathic pulmonary fibrosis (IPF) in the elderly. Although the causes of this increased risk are not well-defined, both ageing and IPF have been associated with shortening of telomeres due to telomerase deficiency. Thoracic imaging with high-resolution computed tomographic (HRCT) scanning plays a key role in the diagnosis of ILD in the elderly, and a characteristic appearance of the lung parenchymal changes on HRCT may provide a confident diagnosis and obviate the need for invasive testing such as surgical lung biopsy. An effective treatment for IPF remains elusive, but many patients will benefit from supportive care and treatment of various co-morbid conditions that are often found in patients with IPF.